Comparing the Timing of Electromyographic Activity of Selected Lumbar-Pelvic Muscles During a Cross-cutting Maneuver in Football Players With Athletic Groin Pain and Healthy Peers - Elham Shirzad Araghi; Hamidreza Naserpour; Mehdi Khaleghi Tazji; Amir Letafatkar (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Athletic groin pain (AGP) is one of the most common injuries among athletes. It causes the use of compensatory mechanisms to adjust pain and affects lumbar-pelvic and hip movements, which leads to prolonging the pain healing process. This study aims to compare the timing of electromyographic activity in selected lumbar-pelvic muscles during a cross-cutting maneuver in football players with AGP and healthy peers.Methods In this quasi-experimental study, 28 football players in the second division league of Iran participated in two groups of control (n=14) and AGP (n=14). The timing of electromyography activity in the gluteus medius, adductor longus, rectus abdominis, multifidus, and transverse abdominis/internal oblique during a cross-cutting maneuver was recorded bilaterally with a one-minute interval since the time of foot-ground contact in two groups.Results The time for the onset of activity in the gluteus medius muscle in the dominant foot (P=0.033) and in the multifidus muscle in the opposite foot (P= 0.023) for the AGP group was significantly delayed in compared to the control group; however, the rectus abdominis muscle in the dominant foot was activated significantly earlier and before the heel contact with the ground (P=0.001).Conclusion It seems that AGP changes the timing of electromyographic muscle activity in football players. These changes and compensatory mechanisms may put the athletes at the potential risk of lower limb injuries. It is recommended to find solutions to reduce the effects of AGP and the resulting changes.